Profile of Students' Mathematical Literacy Based on Level of Mathematical Connection Ability - Nabilah, Wardatun; Faradiba, Surya Sari; Fuat, Fuat; Risalah, Dewi; Widjajanti, Kristina (JME (Journal of Mathematics Education), 2024)
The purpose of this study was to describe students' mathematical literacy abilities based on the level of mathematical connection ability using a qualitative descriptive approach. The researcher as the main instrument was assisted by test questions to measure the ability to connect mathematics and mathematical literacy, as well as interviews. The research subjects were 3 class IX students of SMP Islam Pakis. Subject selection was made based on high, medium, and low levels of mathematical connection ability. The results showed: The selection of research subjects was carried out by purposive sampling technique based on high, medium, and low levels of mathematical connection ability. The results of the data analysis obtained: (1) students at a high level of mathematical connection succeeded in achieving all indicators of mathematical literacy ability, such as being able to identify the information contained in the problem, make mathematical models, do reasoning, use symbols, design and implement appropriate problem strategies, summarizing the results, as well as conducting evaluations; (2) students who are categorized in the moderate level of mathematical connection ability are able to achieve five of the seven indicator components contained in mathematical literacy ability; (3) students who belong to a low level of mathematical connection ability are only able to achieve three of the seven indicator components needed in literacy skills.